Glacigenic postglacial faulting at Saint John, New Brunswick - Broster, B. E.; Burke, K. B. S. (Atlantic Geoscience, 1990)
Displaced glacial striae were examined at outcrops within the central area of Saint John, New Brunswick. Displacements are mostly confined to north-facing slopes of small bedrock hills left after the glacial erosion of Cambrian-Early Ordovician rocks in the southeast limb of a syncline. The striae are generally offset by high-angle reverse faults a few metres in length and with throws up to 60 mm. The faults trend parallel to bedding and dip southward at angles similar to the dip of individual beds. The displacements have long been considered as evidence of postglacial tectonic stresses in the area. However, from a detailed analysis of the extent and orientation of the small faults, we propose that the displacements represent the response of multilayered sedimentary rocks with anisotropic strengths, to differential rates of glacitec tonic loading and unloading. Therefore, the last major displacements likely occurred very soon after deglaciation of the area. RÉSUMÉ On a examiné les déplacements affectant des striures glaciaires sur des affleurements situés en plein centre de Saint-Jean, au Nouveau-Brunswick. Ces déplacements sont surtout confines aux versants nord de petits môles modelés par l’érosion gladaire des rohes cambriennes à éo-ordovciennes danns le flanc sud-est d’unsynclinal. Les striures sont généralement affectées par des failles inverses à fort pendage, d’une longueur de quelques métres et dont le re jet atteint 60 mm. Les failles sont parallèles au litage et penchent vers le sud avec des inclinaisons semblables aux pendages des lits individuels. On a longtemps vu dans ces déplacements le signe évident de contraintes tectoniques postglaciaires dans cette région. Cependant, une analyse détaillée de l’étendue et de l’orientation des petites failles nous permet d’avancer que les déplacements représentent la réponse de roches sédimentaires, disposers en couches multiples et dotées de résistances anisotropes, à divers taux de chargement et de délestage glaciotectoniques. Les demiers déplacements majeure se manifestèrent vraisemblablement très tot après la déglaciation de la région. [Traduit par le journal]